A comparative study of the crystallinity of polyetheretherketone by using density, DSC, XRD, and Raman spectroscopy techniques. (January 2021) - Doumeng, M.; Makhlouf, L.; Berthet, F.; Marsan, O.; Delbé, K.; Denape, J.; Chabert, F.
Abstract: A comparative study of the crystallinity of Polyetheretherketone by using density, DSC, XRD, and Raman spectroscopy techniques. In this work, the microstructure of Polyetheretherketone is first analyzed with usual techniques such as density, Differential Scanning Calorimetry, X-ray Diffraction, and secondly, compared with Raman Spectroscopy. Assessing the degree of crystallinity of PEEK is challenging because of the different interpretation of the crystallinity according to each technique. The density measurement gives the highest most trusted absolute uncertainty for the degree of crystallinity, around 4%, compared to the other techniques. The Differential Scanning Calorimetry, usually used by the polymer community, overestimates up to 18% the degree of crystallinity due to a competitive phenomenon between crystallization and melting of PEEK over the same temperature range, and a fast crystallization. When Analyzing the X-ray Diffraction data, the degree of crystallinity is underestimated up to 11% as a consequence of the broad amorphous halo. Lastly, our investigation proves that Raman microspectroscopy is appropriate to determine the local crystallinity on the sample surface and compares 18 indicators in the same study. The 1651 cm - 1 band shift has the highest correlation coefficient of 0.92 with the degree of crystallinity determined by density. This work attempts to correlate the results of degree of crystallinity of PEEK obtained by these four techniques in order to establish the best evaluation of this fundamental property for numerous applications. Highlights: An original comparative analyse of PEEK microstructure with four techniques: density, DSC, XRD, Raman spectroscopy. The Differential Scanning Calorimetry gives overestimate the value of the degree of crystallinity. The X-ray diffraction gives underestimate the value of the degree of crystallinity. Local characterization of the degree of crystallinity with Raman spectroscopy. The band displacement at 1651 cm-1 of Raman spectroscopy has the highest correlation with the degree of crystallinity.